Vapour–liquid jointed solution for the evaporation–condensation problem. (October 2019) - Shishkova, Irina N.; Kryukov, Alexei P.; Levashov, Vladimir Yu.
Highlights: A new approach for the vapour-liquid jointed solution of heat and mass transfer problem for condensed-phase and the vapour is presented. This method gives the possibility to describe liquid (solid) and vapour region on the base of uniform approach. The distributions of macroparameters at different points in time for evaporation–condensation problems are presented. Abstract: In this paper, an approach for jointly solving liquid and vapour kinetic equations is presented. The particle–interface interaction characteristics are studied. Particle behaviour on the condensed-phase surface are analysed to determine the distribution functions for the evaporating molecules. Different nonsteady evaporation–condensation problems are solved. At this, temperatures of the condensed phase layers begin to change, as do conditions at the interface; therefore, the intensity of the evaporation changes. The processes in the liquid phase influenced the vapour density profiles. Finally, the distributions of macroparameters at different time points are obtained. The proposed approach in this paper can be used in different applications, where evaporation and condensation processes take places, and can be applied in situations far from equilibrium conditions. Also this method can be used as a single algorithm for liquid and vapor description without special attention to liquid-vapor interface (in contrast of a molecular-kinetic approach). Evaporation and condensation phenomena at high enough intensities are important for modern microsystems cooling technologies including liquid films. Liquid droplets evaporation gives another example of such realization. It should be noted that these processes can be observed in wide practical applications under different conditions.